ANALYSIS OF SOURCES OF INVESTMENT SUPPORT FOR INNOVATIVE DEVELOPMENT OF THE NATIONAL ECONOMY REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the problems of investing innovative processes in the national economy of Uzbekistan. In particular, the author analyzed the current state of investment in the innovative development of the national economy, assessed the practice of stimulating innovation and investment activity in Uzbekistan, developed scientific recommendations to increase investment and innovation activity in the sectors of the economy.